Wireless Security in Mobile Health - Osunmuyiwa, Olufolabi; Ulusoy, Ali Hakan (Mary Ann Liebert, Inc, 2012)
Mobile health (m-health) is an extremely broad term that embraces mobile communication in the health sector and data packaging. The four broad categories of wireless networks are wireless personal area network, wireless metropolitan area network, wireless wide area network, and wireless local area network. Wireless local area network is the most notable of the wireless networking tools obtainable in the health sector. Transfer of delicate and critical information on radio frequencies should be secure, and the right to use must be meticulous. This article covers the business opportunities in m-health, threats faced by wireless networks in hospitals, and methods of mitigating these threats.
Keywords: mobile health; wireless security; wireless local area network